Turnover intention among call center employees at AEON Credit Service Butterworth, Penang / Idznie Nasyuha Mohd Izani and Nur Hanis Shahira Fadzil - Mohd Izani, Idznie Nasyuha; Fadzil, Nur Hanis Shahira (2019)
This chapter provides an overview of the study which is consist nine main sections. This chapter identifies the background of the study, ascertain the research problem, research question and the research objective of the research endeavor. It also highlight the significance scope of the study provide definition of terms, and concept used in this study.